VIBRATIONAL AND ROTATIONAL EFFECTS IN THE CL+HOD[--]HCL+OD REACTION - Nyman, G; Clary, D (1994)
Quantum scattering calculations on the Cl+HOD⇌HCl+OD reaction have been performed at collisional energies up to 1.6 eV. The rotating bond approximation is used. In this method, the OD rotation and HCl vibration as well as the bending motion and OH local stretch of HOD are treated explicitly. Here, the theory is extended to account for thermal HOD reactant rotation. The potential energy surface used has accurate reactant and product rovibrational energy levels, correct bond dissociation energies, and a transition state geometry in accord with ab initio data. Mode selectivity is observed - HOD vibrational stretch energy enhances reaction more than vibrational bend energy. Translational energy enhances reaction more than vibrational stretch energy at low total energies, but not generally at higher total energies. Excitation of the local OH stretch in the reactant HOD produces vibrationally excited HCl product. The OD product rotation depends on the reactant HOD rovibrational state. The OD+HCl(v=0) reaction preferentially produces HOD in the vibrational ground state, while the OD+HCl(v=1) reaction preferentially produces HOD with one quantum of vibrational stretch energy. A calculated OH product rotational distribution for the Cl+H2O reaction agrees quite well with experiment. © 1994 American Institute of Physics.